2016
DOI: 10.4028/www.scientific.net/ssp.255.285
|View full text |Cite
|
Sign up to set email alerts
|

Silica Formation during Etching of Silicon Nitride in Phosphoric Acid

Abstract: The etching of silicon nitride using phosphoric acid with silicon dioxide as a mask is an important process step used in the production of 3D NAND devices. This paper examines the theory of formation of a silica film onto the silicon dioxide surface during this etching step by performing a shell balance analysis of silica species in the etched out liquid volume of the 3D NAND structures. The method of moments is used to solve for the moments of the distribution of particle sizes, and this is used to solve for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This phenomenon is believed to be associated with the redeposition of the silica species on the SiO 2 layer instead of SiO 2 layer etching because the concentration of the added silyl-phosphate in the acid solution is significantly close to the silica solubility limit, as depicted in Figure 6d. 6,7,44 As depicted in Figures 6e and S5, the top and cross-sectional views of the SiO 2 layer etched in the 0.18 wt % silyl-phosphate solution exhibited a clean cross section and surface, whereas some globular aggregates were found on the SiO 2 layer etched in the 0.2 wt % silyl-phosphate acid solution. The globular aggregate is believed to be silica species nucleated from the supersaturated acid solution because of the excessive addition of silyl-phosphate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This phenomenon is believed to be associated with the redeposition of the silica species on the SiO 2 layer instead of SiO 2 layer etching because the concentration of the added silyl-phosphate in the acid solution is significantly close to the silica solubility limit, as depicted in Figure 6d. 6,7,44 As depicted in Figures 6e and S5, the top and cross-sectional views of the SiO 2 layer etched in the 0.18 wt % silyl-phosphate solution exhibited a clean cross section and surface, whereas some globular aggregates were found on the SiO 2 layer etched in the 0.2 wt % silyl-phosphate acid solution. The globular aggregate is believed to be silica species nucleated from the supersaturated acid solution because of the excessive addition of silyl-phosphate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…But, as the number of ON stack is increased and the layer thickness is decreased, it is found that it is difficult to etch the SiN x uniformly due to the difficulty in solution penetration by surface tension and leaning of remaining thin SiO 2 layer [10,11]. Also, it was found that some additives used to increase the etch selectivity of SiN x over SiO 2 cause a problem of oxide regrowth [11,12]. Therefore, a dry etching method that is isotropic and highly selective to SiO 2 is required for next generation high density 3D NAND flash memory fabrication [13].…”
Section: Introductionmentioning
confidence: 99%